Substantial Biogeochemical and Biomolecular Processing of Dissolved Organic Matter in an Anticyclonic Eddy in the Northern South China Sea Down to Bathypelagic Depths - Zhang, Miao; Li, Siyu; Hertkorn, Norbert; Harir, Mourad; Xu, Dongfeng; Schmitt-Kopplin, Philippe; Wu, Ying (Frontiers in Marine Science, 2022)
Solid-phase extracted dissolved organic matter (SPE-DOM) was isolated from two depth profiles at the core and at the edge of an anticyclonic eddy (ACE) in the northern South China Sea. Non-target nuclear magnetic resonance (NMR) spectroscopy and Fourier transform ion cyclotron mass spectrometry (FTICR/MS) of SPE-DOM revealed a higher uniformity of DOM molecules within the ACE than at the edge of the ACE. Small-scale upwelling of external nutrients may have contributed to higher productivity and production of fresher DOM, with higher proportions of CHNO and CHNOS compounds and low molecular weight species at the edge of the eddy. Common SPE-DOM molecules of supposedly biological origin such as carbohydrates and olefins were most abundant in the chlorophyll maximum layer in both stations. An unusual suite of 10 abundant and 35 less abundant tert-butyl benzene derivatives with potential to act as endocrine disruptors within a marine food chain and two dozen ketones of putative bacterial origin was recognized at meso- and bathypelagic depths in single-digit micromolar concentrations, with a distinct maximum at 1000 m depth at the edge of ACE. Downwelling might bring temporary large volumes of productive marine waters into deep waters, with micromolar concentration of abundant, microbial food web-specific metabolites (e.g. 2,4-di-tert-butylphenol et al.). In our study, these eventually added up to one quarter of common background biogeochemical marine organic matter even at bathypelagic depths and beneath and are significant food and energy sources for marine biota. Mesoscale chemical heterogeneity of marine water columns might extend to larger depths than currently anticipated and may create activity hotspots influencing biota, processing of DOM, and cycling of nutrients and trace elements.